A History of Australian Co-operatives 1827–2023 - Greg Patmore; Nikola Balnave; Olivera Marjanovic (Routledge, 2024)
Co-operatives provide a different approach to organising business through their ideals of member ownership and democratic practice. Every co-operative member has an equal vote regardless of his or her own personal capital investment. They take a variety of different forms, including consumer co-operatives, agricultural co-operatives, worker co-operatives and financial co-operatives. Patmore, Balnave and Marjanovic provide a perspective on Australian co-operative development within a conceptual framework and international context since the 1820s by exploring the economic, political and social factors that explain their varying fortunes. Drawing upon the Visual Historical Atlas of Australian Co-operatives, a significant database of Australian co-operatives and a variety of historical sources, this book provides a detailed historical analysis of their development, from their inception in Australia to today. Australian co-operatives were heavily dependent on state sympathy for their growth and vulnerable to ideas that challenged collective organisation such as Neo-liberalism. Despite these challenges, the co-operative business model has persisted and since 2009, there has been resurgence of interest and organisation that may provide a platform for future growth. A useful resource for practitioners, students, educators, policy makers and researchers that highlights a significant alternative business model to the Investor-Owned Business and state enterprise. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.
Keywords: 330; cooperatives; coop; civil society; non-profit; public; Visual Historical Atlas of Australian Co-operatives; alternative business models